Community prevalence of long‐term urinary catheters use in England. Issue 2 (15th February 2016) - Gage, Heather; Avery, Miriam; Flannery, Caragh; Williams, Peter; Fader, Mandy
Abstract : Objectives: To calculate the prevalence of long term catheter use in the community in two areas in the south and west of England. Subjects/patients (or materials) and methods: People in England register with general practices to access health care through a National Health Service. Catheters are provided by prescription free of charge. In 2008, patients using urinary catheters for over 3 months were identified, and demographic information collected, from databases of general practices, using catheter prescribing records. The age and sex distributions of people in each practice were obtained from capitation claims. Overall, and age and sex‐specific prevalence were calculated separately for each area, and compared. Results: A total of 583 long term catheter users (329 south, 254 west) were identified from 404, 328 people registered with practices. The overall population prevalence is similar in both locations (0.146% southern, 0.141% western). Extrapolating for the United Kingdom, this is over 90, 000 long term catheter users. Prevalence increases with age (0.732% in over 70 years, 1.224% over 80), especially amongst men. Overall, higher proportions have neurological (vs. non‐neurological) reasons (62.9% vs. 37.1%) and use urethral (vs. suprapubic) catheters (59.7% vs. 40.3%). Compared to men, more women tend to use suprapubic (56.4% vs. 29.3%) and have a catheter for neurological reasons (71.8% vs. 56.2%, P  = 0.053). Conclusions: Previous evidence on prevalence of long term catheter use is sparse, and of variable quality. The strength of this study is utilisation of a reliable source of data (catheter prescriptions) from a large population of patients. Neurourol. Urodynam. 36:293–296, 2017 . © 2016 Wiley Periodicals, Inc.